2016
DOI: 10.1007/s00134-016-4571-5
|View full text |Cite|
|
Sign up to set email alerts
|

Potentially modifiable factors contributing to outcome from acute respiratory distress syndrome: the LUNG SAFE study

Abstract: ClinicalTrials.gov NCT02010073.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
217
3
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(255 citation statements)
references
References 31 publications
20
217
3
15
Order By: Relevance
“…There is a high variability in reported mortality of ARDS patients, probably reflecting differences in care, risk factors, ability to diagnose, and resource availability. However, in general, recent studies suggest a decrease in mortality rate from ARDS probably due to better ventilatory care and control of modifiable risk factors associated with mortality [15].…”
mentioning
confidence: 99%
“…There is a high variability in reported mortality of ARDS patients, probably reflecting differences in care, risk factors, ability to diagnose, and resource availability. However, in general, recent studies suggest a decrease in mortality rate from ARDS probably due to better ventilatory care and control of modifiable risk factors associated with mortality [15].…”
mentioning
confidence: 99%
“…The association of ΔP with mortality in ARDS patients was confirmed in another large observational study [2]. Other studies also showed that high ΔP may detect lung overstress [3] and be associated with high morbidity [4].…”
Section: Introductionmentioning
confidence: 68%
“…All Tunisian and Moroccan ICUs that have taken part in such surveys are in university hospitals. In the area of respiratory medicine (organ system support and treatment), various departments of critical care medicine have joined European Society of Intensive Care Medicine trial groups (LUNG SAFE Investigators) and the VENTILA Group Consortium in the realization of international observational studies focusing on mechanical ventilation and acute respiratory distress syndrome (incidence, ventilation modalities, and outcome) [8,9].…”
Section: The Current State Of Researchmentioning
confidence: 99%